Effect of concomitant usage of alteplase and mechanical thrombectomy for M1 middle cerebral artery occlusion on clinical outcome: a retrospective analysis of 457 patients from two centers - Pikija, Slaven; Killer-Oberpfalzer, Monika; Pfaff, Johannes A. R.; Griessenauer, Christoph J.; Sonnberger, Michael; Vosko, Milan; Mutzenbach, Johannes S.; Schwarzenhofer, Daniel; Hecker, Constantin (Frontiers in Neurology, 2024)
Abstract Introduction Endovascular thrombectomy (EVT) and concomitant usage of intravenous alteplase (alteplase) in large vessel occlusion stroke may produce unwanted excess intracerebral hemorrhage (ICH). Whether this applies specifically to isolated occlusion of the M1 segment of the middle cerebral artery (MCA) is unknown. Methods A retrospective study from two tertiary thrombectomy centers. ICH was determined according to Heidelberg Bleeding Classification (HBC). Factors associated with the occurrence of ICH in EVT alone vs. EVT with alteplase were evaluated using logistic regression analysis. Factors related to the clinical outcome as determined with a modified Rankin scale (mRS) were investigated with univariate and adjusted multivariate logistic regression analysis. The interaction between clinical variables and the usage of alteplase on the occurrence of ICH was evaluated. Results Any ICH occurred in 156/457 (34.1%) patients Class 1a bleeding in 37 (8.1%), type 2 in 45 (9.8%) Class 1c in 22 (4.8%), Class 2 in 25 (5.5%), and Class 3 (extraparenchymal) in 27 (5.9%). ICH occurred in similar frequency between alteplase-treated patients vs. EVT alone (85/262 [32%] vs. 71/195 [36%]; OR 1.19 (95% CI 0.81-1.76). After adjustment, odds for clinical outcome were lower in ICH patients (OR 0.44 [95% CI 0.25-0.74]), p=0.002). Higher ICH rate was associated with more EVT steps (p for interaction -.005), and usage of only stent-retriever (p for interaction =0.005). Conclusion Utilization of alteplase alongside EVT for MCA M1 occlusion did not result in excessive ICH occurrences or clinical deterioration.